Preparation method of hard-soft carbon coated silicon carbon negative electrode material
By performing double-layer coating of soft carbon and hard carbon on silicon carbon negative electrode material, the problem of poor volume expansion and cycle life of silicon carbon material is solved, significantly improving its magnification and cycling performance, and achieving better electrochemistry performance.
Patent Information
- Application Number
- CN202411284913.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Silicon-carbon negative electrode materials have problems of volume expansion effect and poor cycle life in lithium-ion batteries, which affect their rate performance.
By double-layer coating of soft carbon and hard carbon on the silicon and graphite mixture, carbonization is carried out with asphalt and sucrose at high temperatures, forming a hard-soft carbon coated silicon carbon negative electrode material, inhibiting silicon volume expansion and improving the material cycle and rate performance.
It effectively suppresses the volume expansion of silicon, significantly improves the magnification and circulation performance of the material, and optimizes the charge and discharge performance.
Smart Images

Figure BDA0005042842280000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of negative electrode materials, and in particular relates to a method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material. Background Art
[0002] Silicon-carbon anode material is a new type of lithium-ion battery anode material, composed of silicon-based active materials and carbon-based conductive materials. The theoretical capacity of silicon-based anode is as high as 3580m·Ah / g, and it is expected to replace graphite as the next generation of high-energy density lithium-ion battery anode material. However, silicon-carbon anode also has problems such as volume expansion effect and poor cycle life. When silicon and lithium undergo electrochemical reaction, its volume may expand to 300%, so it is considered that coating a layer of silicon-carbon on the surface of artificial graphite anode material can further improve the specific capacity of artificial anode material.
[0003] Asphalt is used as a binder and the thin carbon layer obtained after carbonization can improve the conductivity of the material and alleviate the volume expansion of the material to a certain extent, which helps to improve the charge and discharge performance of silicon-carbon materials. However, the residual carbon value provided by the soft carbon structure formed by asphalt during the high-temperature carbonization process is relatively low, which affects the rate performance. Summary of the invention
[0004] Based on the above technical problems, the present invention successively performs soft and hard carbon coating on a mixture of silicon and graphite using asphalt and sucrose. The hard-soft carbon-coated silicon-carbon negative electrode material obtained thereby can not only inhibit the volume expansion of silicon, but also exhibit more excellent rate performance and cycle performance.
[0005] The specific scheme of the present invention is as follows:
[0006] The present invention provides a method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, comprising: S1, mixing nano-silicon and graphite to obtain silicon-carbon mixed powder; S2, dissolving asphalt in anhydrous ethanol, and then mixing it with the silicon-carbon mixed powder and then carbonizing it; S3, dissolving sucrose in water, and then mixing it with the composite material obtained in S2 and then carbonizing it to obtain a hard-soft carbon-coated silicon-carbon negative electrode material; wherein the carbonization temperature in S2 and S3 is both 1200-1300°C.
[0007] Preferably, in S1, the graphite is artificial graphite; the mass ratio of nano-silicon to graphite is 10-12:88-90; and the D50 of the graphite is 9-11 μm.
[0008] Preferably, in S1, when nano-silicon and graphite are mixed, the rotation speed is 500-700 rpm and the mixing time is 20-30 min.
[0009] Preferably, in S2, the mass ratio of asphalt to silicon-carbon mixed powder is 3-4:100, and the mass volume ratio of asphalt to anhydrous ethanol is 3-4:150-200 in g / mL.
[0010] Preferably, the D50 of the composite material obtained in S2 is 13-15 μm.
[0011] Preferably, in S3, the mass volume ratio of sucrose to water is 3-4:150-200 in g / mL; the mass ratio of sucrose to the composite material obtained in S2 is 3-4:95-100.
[0012] Preferably, in S2, the asphalt dissolved in anhydrous ethanol and the silicon-carbon mixed powder are mixed at a speed of 400-500 r / min and a mixing time of 300-360 min; in S3, the sucrose dissolved in water and the composite material described in S2 are mixed at a speed of 300-400 r / min and a mixing time of 150-180 min.
[0013] Preferably, the asphalt in S2 is an asphalt-loaded porous silica composite material, and its preparation method includes: (1) crushing the asphalt, adding hydrogen peroxide to mix, heating in a water bath to react, and obtaining oxidized asphalt; (2) dissolving hexadecyltrimethylammonium bromide in deionized water, adding ammonium hydroxide, stirring and mixing, and then adding ethanol, and then adding tetraethyl orthosilicate and oxidized asphalt and stirring for 3-6 hours to obtain an asphalt-loaded porous silica composite material.
[0014] Preferably, in step (1), the mass volume ratio of asphalt to hydrogen peroxide is 1:2-4 in g / mL; the temperature of the water bath reaction is 65-75° C., and the reaction time is 1.5-3.5 h.
[0015] Preferably, in step (2), the mass ratio of hexadecyltrimethylammonium bromide, ammonium hydroxide, ethanol, tetraethyl orthosilicate and oxidized asphalt is 20-30:40-65:80-100:6.5-10:30-40.
[0016] Preferably, the carbonization treatments in S2 and S3 are both carried out under a protective atmosphere, the carbonization treatment temperature is 1200° C., and the carbonization treatment time is 330-360 min.
[0017] Preferably, the temperature rise curve of the carbonization treatment in S2 and S3 is: heating from room temperature to 100°C for 10 minutes; then heating to 200°C for 10 minutes; further heating to 300°C for 10 minutes; keeping at 300°C for 180 minutes; heating from 300 to 1200°C for 120 minutes; keeping at 1200°C for 360 minutes.
[0018] The beneficial effects of the present invention are:
[0019] The double-layer coated silicon-carbon negative electrode material obtained by coating soft carbon and hard carbon on the outer layer of the silicon and graphite mixture can not only inhibit the volume expansion of silicon, but also show more excellent rate performance and cycle performance. In a preferred embodiment, the soft carbon is obtained by carbonizing a porous silica composite material supported by asphalt as a precursor, and the soft carbon obtained has a porous structure, which is conducive to the uniform coating of the outer hard carbon. DETAILED DESCRIPTION
[0020] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0021] Example 1
[0022] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, comprising:
[0023] S1. Weigh 10 g of nano-silicon powder and 90 g of artificial graphite powder (D50: 9-11 um) and mix them thoroughly using a laboratory high-speed mixer SMB10 (Songyuan Machinery) to form a nano-silicon / artificial graphite mixed powder. Set the speed to 650 rpm and the time to 25 min.
[0024] S2. Weigh 3 g of asphalt (Aoshenglong), add it to 180 ml of anhydrous ethanol, use a magnetic stirrer to fully stir and dissolve, set the speed to 700 r / min, set the temperature to 65°C, and the time to 70 min.
[0025] The nano-silicon / artificial graphite mixed powder prepared in step 1 was slowly added to the anhydrous ethanol in which the asphalt was dissolved, and wet mixed using a planetary ball mill (Feichi), with the speed set to 420 / min and the time set to 330 min.
[0026] The mixed materials are placed in an oven for drying at 100°C for 120 minutes. Then, a muffle furnace is used for carbonization and a nitrogen atmosphere is provided throughout the process. The heating curve is set as follows: room temperature to 100°C, heating for 10 minutes; heating to 200°C, heating for 10 minutes; then heating to 300°C, heating for 10 minutes; keeping at 300°C for 180 minutes; heating from 300 to 1200°C for 120 minutes; keeping at 1200°C for 360 minutes. Then, the atmosphere is kept naturally cooled to room temperature to obtain a carbon-coated nano-silicon / artificial graphite composite material, which is then crushed to obtain a powder with an average particle size (D50) of 13 to 15 um.
[0027] S3, weigh 3g of sucrose, add it to 160ml of deionized water, use a glass rod to stir and dissolve it, then add 100g of the carbon-coated nano-silicon / artificial graphite composite material prepared in step 2, use a planetary vacuum mixer (MSK-SFM-16) to mix and stir, set the speed to 320r / min, and the time is 180min.
[0028] The mixed materials were placed in an oven for drying at 100°C for 120 min. Then, carbonization was performed in a muffle furnace and nitrogen atmosphere protection was performed throughout the process. The heating curve was set the same as step S2. Then, the atmosphere was kept to cool naturally to room temperature to obtain a hard-soft carbon-coated nano-silicon / artificial graphite composite material, which was then crushed to obtain a powder with an average particle size (D50) of about 13 to 15 um.
[0029] Example 2
[0030] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, comprising:
[0031] S1. Weigh 10 g of nano-silicon powder and 90 g of artificial graphite powder (D50: 9-11 um) and mix them thoroughly using a laboratory high-speed mixer SMB10 (Songyuan Machinery) to form a nano-silicon / artificial graphite mixed powder. Set the speed to 700 rpm and the time to 20 min.
[0032] S2. Weigh 4 g of asphalt (Aoshenglong), add it to 200 ml of anhydrous ethanol, use a magnetic stirrer to fully stir and dissolve, set the speed to 600 r / min, set the temperature to 70°C, and the time to 85 min.
[0033] The nano-silicon / artificial graphite mixed powder prepared in step 1 was slowly added to the anhydrous ethanol in which the asphalt was dissolved, and wet mixed using a planetary ball mill (Feichi), with the speed set to 500 / min and the time set to 300 min.
[0034] The mixed materials were placed in an oven for drying at 100°C for 120 min. Then, carbonization was performed in a muffle furnace under nitrogen atmosphere protection, and the heating curve was set to be the same as that in Example 1 to obtain a carbon-coated nano-silicon / artificial graphite composite material, which was then crushed to obtain a powder with an average particle size (D50) of 13 to 15 um.
[0035] S3, weigh 4g of sucrose, add it to 200ml of deionized water, use a glass rod to stir and dissolve it, then add 100g of the carbon-coated nano-silicon / artificial graphite composite material prepared in step 2, use a planetary vacuum mixer (MSK-SFM-16) to mix and stir, set the speed to 400r / min, and the time to 160min.
[0036] The mixed materials were placed in an oven for drying at 100°C for 120 min. Then, carbonization was performed in a muffle furnace with nitrogen atmosphere protection throughout the process. The heating curve was set the same as in Example 1 to obtain a hard-soft carbon-coated nano-silicon / artificial graphite composite material, which was then crushed to obtain a powder with an average particle size (D50) of 13 to 15 um.
[0037] Example 3
[0038] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, which differs from Example 1 only in that the asphalt in S2 is an asphalt-loaded porous silica composite material, and the other steps and parameters are the same as those in Example 1.
[0039] The method for preparing the asphalt-loaded porous silica composite material comprises:
[0040] (1) After the asphalt is ball-milled and crushed, hydrogen peroxide is added to the mixture, and the mixture is heated in a water bath at 70° C. for 2 h, and then dried to obtain oxidized asphalt; the mass volume ratio of asphalt to hydrogen peroxide is 1:3.5 in g / mL;
[0041] (2) Dissolve hexadecyltrimethylammonium bromide in deionized water, add ammonium hydroxide, stir and mix, then add ethanol, continue stirring, then add tetraethyl orthosilicate and oxidized asphalt and stir for 4 hours to obtain an asphalt-loaded porous silica composite material, wherein the mass ratio of hexadecyltrimethylammonium bromide, ammonium hydroxide, ethanol, tetraethyl orthosilicate and oxidized asphalt is 25:60:98:8.5:40.
[0042] Comparative Example 1
[0043] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, comprising:
[0044] S1, the same as in Example 1;
[0045] S2. Weigh 3 g of asphalt (Aoshenglong), add it to 180 ml of anhydrous ethanol, use a magnetic stirrer to fully stir and dissolve, set the speed to 700 r / min, set the temperature to 65°C, and the time to 70 min;
[0046] Weigh 3 g of sucrose, add it to 160 ml of deionized water, and stir thoroughly with a glass rod to dissolve;
[0047] The nano-silicon / artificial graphite composite powder prepared in step 1 was mixed with anhydrous ethanol for dissolving asphalt and deionized water for dissolving sucrose, and wet-mixed using a planetary ball mill (Feichi), with a speed of 420 / min and a mixing time of 330 min.
[0048] The mixed materials were placed in an oven for drying at 100°C for 120 min. Then, carbonization was performed in a muffle furnace and nitrogen atmosphere protection was performed throughout the process. The heating curve was set to be the same as S2 in Example 1. Then, the atmosphere was kept to cool naturally to room temperature to obtain a hard-soft carbon-coated nano-silicon / artificial graphite composite material, which was then crushed to obtain a powder with an average particle size (D50) of about 13 to 15 um.
[0049] Comparative Example 2
[0050] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material. Compared with Example 1, the only difference is that the amount of asphalt added in S2 is adjusted from 3g to 1g, and the other steps and parameters are the same as those in Example 1.
[0051] Comparative Example 3
[0052] A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material. Compared with Example 1, the only difference is that the amount of asphalt added to S2 is adjusted from 3g to 5g, and the other steps and parameters are the same as those in Example 1.
[0053] Performance Testing:
[0054] The negative electrode material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) prepared above were stirred and mixed in a mass ratio of 90:5:5, wherein PVDF was dissolved with an appropriate amount of N-methylpyrrolidone (NMP). The mixed slurry was evenly coated on the pre-punched copper foil, and after being dried in a vacuum drying oven at 110°C for 12 hours, it was weighed and used as the positive electrode of the simulated battery, the metal lithium sheet was used as the negative electrode, the diaphragm was Celgard 2400, and the electrolyte was 1 mol / L LiPF6 (EC:DMC volume ratio was 1:1). In a glove box filled with argon and deoxygenated and dehydrated, button cells CR 2016 were assembled for electrochemical testing. The electrolyte was a solution of LiPF6 in ethylene carbonate and dimethyl carbonate (volume ratio was 1:1). The test results are shown in Table 1 below.
[0055] Table 1. Comparison of electrochemical performance data
[0056]
[0057] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material, characterized in that: include: S1, mixing nano silicon and graphite to obtain silicon-carbon mixed powder; S2, dissolving asphalt in anhydrous ethanol, and then mixing it with the silicon-carbon mixed powder and then carbonizing it; S3, dissolving sucrose in water, and then mixing it with the composite material obtained in S2 and then carbonizing it to obtain a hard-soft carbon-coated silicon-carbon negative electrode material; wherein the carbonization temperature in S2 and S3 is 1200-1300°C.
2. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1, characterized in that: In S1, the graphite is artificial graphite; the mass ratio of nano-silicon to graphite is 10-12:88-90; and the D50 of the graphite is 9-11 μm.
3. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: In S1, when nano-silicon and graphite are mixed, the rotation speed is 500-700 rpm and the mixing time is 20-30 min.
4. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: In S2, the mass ratio of asphalt to silicon-carbon mixed powder is 3-4:100, and the mass volume ratio of asphalt to anhydrous ethanol is 3-4:150-200 in g / mL.
5. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The D50 of the composite material obtained by S2 is 13 to 15 μm.
6. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: In S3, the mass volume ratio of sucrose to water is 3-4:150-200 in g / mL; the mass ratio of sucrose to the composite material obtained in S2 is 3-4:95-100.
7. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The asphalt described in S2 is an asphalt-loaded porous silica composite material, and its preparation method includes: (1) crushing the asphalt, adding hydrogen peroxide to mix, heating in a water bath to react, and obtaining oxidized asphalt; (2) dissolving hexadecyltrimethylammonium bromide in deionized water, adding ammonium hydroxide, stirring and mixing, and then adding ethanol, and then adding tetraethyl orthosilicate and oxidized asphalt and stirring for 3-6 hours to obtain an asphalt-loaded porous silica composite material.
8. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 7, characterized in that: In step (1), the mass volume ratio of asphalt to hydrogen peroxide is 1:2-4 in g / mL; the temperature of the water bath reaction is 65-75° C., and the reaction time is 1.5-3.5 h.
9. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 7, characterized in that: In step (2), the mass ratio of hexadecyltrimethylammonium bromide, ammonium hydroxide, ethanol, tetraethyl orthosilicate and oxidized asphalt is 20-30:40-65:80-100:6.5-10:30-40.
10. The method for preparing a hard-soft carbon-coated silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The carbonization treatments in S2 and S3 are both carried out under a protective atmosphere, the carbonization treatment temperature is 1200° C., and the carbonization treatment time is 330-360 min.
Citation Information
Patent Citations
Silicon-carbon alloy cathode material for lithium ion batteries and preparation method thereof
CN101969111A
Preparation and application of lithium battery silicon-carbon composite material taking synthetic graphite as carrier
CN103346305A
Silicon-carbon composite material as well as preparation method and application thereof
CN115275175A
Preparation method of silicon-carbon negative electrode material and silicon-carbon negative electrode material
CN117239048A
High-capacity and long-life silicon-carbon negative electrode material and preparation process thereof
CN117239088A
Cited By
Preparation process of fast-charging negative electrode material
CN119764400A
Preparation process of fast-charging negative electrode material
CN119764400B
Preparation method of high-stability silicon-carbon material
CN120048887A
Soft carbon and hard carbon co-coated nanometer silicon negative electrode material and preparation method thereof
CN121076094A
